2020
DOI: 10.1111/his.14012
|View full text |Cite
|
Sign up to set email alerts
|

SATB2 protein expression by immunohistochemistry is a sensitive and specific marker of appendiceal and rectosigmoid well differentiated neuroendocrine tumours

Abstract: Aims Neuroendocrine neoplasms (NNs) range from well to poorly differentiated and indolent to highly aggressive. The site of origin in metastatic NNs has therapeutic and prognostic implications. SATB2 is a transcriptional regulator involved in osteoblastic and neuronal differentiation and is a sensitive and specific marker of colorectal epithelium. This study aimed to evaluate the expression of SATB2 in NNs from various primary sites and its utility as a marker in determining the site of origin of these neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…5-7 Other studies have reported that SATB2 are positive in 53% of Genitourinary small cell carcinoma, 27% of colorectal NECs and 25% of Pancreatic NECs. 7,29 Similarly pulmonary SCLC or pulmonary NEC (details not shown) have shown the positive rate of SATB2 ranging from 21% to 33%. 5,7 Besides, a most recent study has reported the expression of SATB2 in pulmonary and thymic neuroendocrine tumors (carcinoid tumor and NEC), with a higher percentage of expression in SCLC comparing to the previous reports.…”
Section: Discussionmentioning
confidence: 94%
“…5-7 Other studies have reported that SATB2 are positive in 53% of Genitourinary small cell carcinoma, 27% of colorectal NECs and 25% of Pancreatic NECs. 7,29 Similarly pulmonary SCLC or pulmonary NEC (details not shown) have shown the positive rate of SATB2 ranging from 21% to 33%. 5,7 Besides, a most recent study has reported the expression of SATB2 in pulmonary and thymic neuroendocrine tumors (carcinoid tumor and NEC), with a higher percentage of expression in SCLC comparing to the previous reports.…”
Section: Discussionmentioning
confidence: 94%
“…Bayrak R et al analyzed 118 colorectal, 59 gastric, and 32 pancreatic adenocarcinoma resection specimens and concluded that in colorectal adenocarcinomas, CDX2 expression and the CK7−/CK20 + pattern were highly sensitive and speci c [31] . SATB2, a recently described transcriptional regulator, is reported as a highly speci c and sensitive marker of colorectal cancer (CRC) [36,37] . Magnusson K et al reported that SATB2 plus CD20 + could detect over 95% of the CRC cases [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Bayrak et al [ 24 ] analyzed 118 colorectal, 59 gastric and 32 pancreatic adenocarcinoma resection specimens and concluded that in colorectal adenocarcinoma, CDX2 expression and the CK7 − /CK20 + pattern were highly sensitive and specific. SATB2, a recently described transcriptional regulator, is reported as a highly specific and sensitive marker of colorectal cancer (CRC)[ 27 ]. Magnusson et al [ 28 ] reported that SATB2 plus CD20 + could detect > 95% of the CRC cases.…”
Section: Discussionmentioning
confidence: 99%